Through the back door: Unconventional protein secretion - Michael J. Cohen; William J. Chirico; Peter N. Lipke (The Cell Surface, 2020)
Proteins are secreted from eukaryotic cells by several mechanisms besides the well-characterized classical secretory system. Proteins destined to enter the classical secretory system contain a signal peptide for translocation into the endoplasmic reticulum. However, many proteins lacking a signal peptide are secreted nonetheless. Contrary to conventional belief, these proteins are not just released as a result of membrane damage leading to cell leakage, but are actively packaged for secretion in alternative pathways. They are called unconventionally secreted proteins, and the best-characterized are from fungi and mammals. These proteins have extracellular functions including cell signaling, immune modulation, as well as moonlighting activities different from their well-described intracellular functions. Among the pathways for unconventional secretion are direct transfer across the plasma membrane, release within plasma membrane-derived microvesicles, use of elements of autophagy, or secretion from endosomal/multivesicular body-related components. We review the fungal and metazoan unconventional secretory pathways and their regulation, and propose experimental criteria to identify their mode of secretion.